Examining the Impact of Teacher’s Training Programs on the Role of Teachers in the Implementation and Development of Curriculum (Journal of Education and Educational Development, 2024)
Teachers’ training programs are widely recognized as essential for professional development and growth. This study aimed to explore how these programs affect teachers’ ability to implement the curriculum effectively. A key focus was observing teachers’ attitudes toward curriculum implementation following their training. The study assesses the quality of training programs designed to equip teachers as skilled curriculum developers and evaluates how effectively these programs support teachers in planning, designing, and implementing the curriculum. Using a quantitative approach with a close-ended questionnaire, data were gathered from 250 teachers and school leaders selected through purposive sampling. The findings suggest that while teacher training programs prepare educators for traditional teaching methods, they fall short in developing teachers as curriculum designers. Moreover, the study shows that teachers are not fully involved in all stages of curriculum planning and development. The insights from this research may be valuable for those interested in curriculum development and could guide policymakers in designing training programs that include relevant content and practical experience, enabling teachers to become proficient curriculum designers.